Cultural Presentation of the Muslim Middle Class in Contemporary Indonesia - Hasbullah, Moeflich (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
One approach to understanding the platform of New Order politics is to view it as having been a contest between Indonesian Political groups for access to power. Throughout the New Order period, economic capital was largely in the hands of a Chinese minority, while political capital was in the hands of the abangan Javanese priyayi. At the same time, the santri (the 'true Muslims'), have been economically and politically marginalized. They have been, as Wertheim (1975) put it,